Using residue analysis to explore household activities at the Harris Site, Mimbres Valley, New Mexico. (June 2018) - Roth, Barbara; Woods, Aaron; Romero, Danielle; McNeely, Malka; Malainey, Mary
Abstract: This paper uses data obtained from several different kinds of residue analyses to explore household activities and evaluate differences and similarities between households at the Harris Site, a Late Pithouse period (550–1000 CE) site located in the Mimbres River Valley of southwestern New Mexico. We used three different methods to explore these topics: lipid analysis from ceramic vessels, spot tests of fatty acids from pithouses, and FTIR from several artifact classes. The results were somewhat mixed, with information obtained on food processing, diet, and formation processes, but in the long run they have provided data that can be used in concert with other analysis data to document household activities and similarities and differences between households through time. Highlights: Three different kinds of residue analyses pithouse floors were used to examine household activities and if differences between households Lipid analysis of ceramic vessels proved to be most useful in documenting food processing activities Fatty acid spot tests of soil samples revealed food processing activities within houses and differences between several households FTIR analysis primarily documented the depositional context of the artifacts